Evidence Based Medicine - Abstracts of Oral Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Evidence Based Medicine at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10173